Seborrheic Keratoses as the First Sign of Bladder Carcinoma: Case Report of Leser-Trélat Sign in a Rare Association with Urinary Tract Cancer - Aline Stollmeier; Bernardo Augusto Rosario; Bruna Loise Mayer; Gibran Avelino Frandoloso; Francisco Luiz Gomide Mafra Magalhães; Gustavo Lenci Marques (Case Reports in Medicine)
Introduction. Skin disorders can be the first manifestation of occult diseases. The recognition of typical paraneoplastic dermatoses may anticipate the cancer diagnosis and improve its prognosis. Although rarely observed, the sudden appearance and/or rapid increase in number and size of seborrheic keratoses can be associated with malignant neoplasms, known as the sign of Leser-Trélat. The aim of this report is to unveil a case of a patient whose recently erupted seborrheic keratoses led to investigation and consequent diagnosis of bladder cancer. Case Presentation. A 67-year-old man was admitted to the intensive care unit due to an exacerbation of chronic obstructive pulmonary disease (COPD). On physical examination, multiple seborrheic keratoses on the back of the hands, elbows, and trunk were observed; the patient had a 4-month history of these lesions yet was asymptomatic. The possibility of Leser-Trélat syndrome justified the investigation for neoplasia, and a bladder carcinoma was detected by CT-scan. The patient denied previous hematuria or any other related symptoms. Many of the lesions regressed during oncologic treatment. Conclusion. Despite the critics on the validity of the sign of Leser-Trélat, our patient fulfills the description of the disease, though urinary malignancy is a rare association. That corroborates the need of further investigation when there is a possibility of paraneoplastic manifestation.